Investigation of heat transfer and pressure drop in a concentric heat exchanger with snail entrance - Durmus, A; Durmus, A; Esen, M (Pergamon-Elsevier Science Ltd, 2002)
In this study, in order to increase heat transfer in concentric double-pipe heat exchangers by passive method, snail which is mounted at inlet of the inner pipe and assumed as a swirl generator was used. In the experimental set-up, cold air in ambient conditions was passed through the inner pipe while hot water was flowing through the annulus. The effects of a snail on the heat transfer and pressure drop were investigated for parallel and counter-flow, and obtained Nusselt numbers (Nu) were compared with those found, using a standard correlation such as Dittus-Boelter equation given for axial flows in smooth pipes. The results were correlated in the form of Nusselt number as a function of Reynolds number, Prandtl number and the swirling angle. An augmentation of up to 120% in Nusselt number was obtained in the swirl flow for counter-flow and 45 swirling angle. Though the swirl flow effect of the snail caused some increase in pressure drop, this effect was unimportant compared with the improvement in heat transfer capacity. (C) 2002 Elsevier Science Ltd. All rights reserved.
Keywords: experimental; concentric heat exchanger; snail; swirl flow; swirling angle; heat transfer enhancement; pumping power